Evaluasi Kebijakan Dana Desa Peraturan Bupati No. 71 Tahun 2016 Kabupaten Semarang: Studi kasus di desa Randugunting Kecamatan Bergas - Dyah Hariani (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2019)
Development is one of the country's benchmarks in the welfare of its people, so development from the village level needs to be done to support equitable development. One of the government's efforts in terms of development is through a village fund program through Semarang Regent Regulation No. 71 of 2016 concerning the procedures for the distribution and determination of village funds in Randugunting Village, Bergas District, Semarang Regency, so that policies need to be evaluated on village fund programs so that they can realize equitable development. This study uses a qualitative method with a descriptive approach. Efforts to provide an assessment or evaluation of village fund policies can be seen through the characteristics of policy evaluations and constraints faced in implementing policy evaluations. The characteristics of policy evaluation consist of a focus on values, interdependence of fact values, present and past orientation, value duality, while the constraints on policy evaluation can be seen from psychological constraints, economic constraints, technical constraints, political constraints, and constraints on evaluation resources. Randugunting Village is an area that needs to be developed, so the variety of considerations are needed to be able to optimize the implementation of village fund program program evaluation in Randugunting Village